RANCANG BANGUN PENJUALAN STRIPING MOTOR RR STRIPING BERBASIS WEB - RESNU ARIZAL, MUHAMMAD; Saefurrohman, Saefurrohman (Information Technology and Telematics, 2018)
ABSTRACT RR Striping is a company engaged in motorcycle striping sales in Semarang. RR Striping sells striping motorcycles from customers who want to buy striping motors by telephone or come directly to RR Striping.The motor striping sales system that is currently running on RR Striping is that customers make motorbike striping purchases by telephone or come directly to RR Striping then the RR Striping will check the availability of motor striping manually, if striping motors are available then customers can buy striping motors, while if striping motorbikes are not available so customers can order striping motors from RR Striping The system development method used in this study is a prototype consisting of analysis, design using DFD and ERD, making prototypes using PHP and MySQL, evaluation and improvement and results. The final result of this research is the design of selling web-based RR Striping striping motorcycles can make it easier for customers to buy striping motors without time and place restrictions and makes it easy for customers to obtain motor striping information on RR Striping quickly and easily.